Global emissions of NH3, NOx, and N2O from biomass burning and the impact of climate change. (2nd January 2021) - Bray, Casey D.; Battye, William H.; Aneja, Viney P.; Schlesinger, William H.
ABSTRACT: Emissions of ammonia (NH3 ), oxides of nitrogen (NOx ; NO +NO2 ), and nitrous oxide (N2 O) from biomass burning were quantified on a global scale for 2001 to 2015. On average biomass burning emissions at a global scale over the period were as follows: 4.53 ± 0.51 Tg NH3 year −1, 14.65 ± 1.60 Tg NOx year −1, and 0.97 ± 0.11 Tg N2 O year −1 . Emissions were comparable to other emissions databases. Statistical regression models were developed to project NH3, NOx, and N2 O emissions from biomass burning as a function of burn area. Two future climate scenarios (RCP 4.5 and RCP 8.5) were analyzed for 2050–2055 ("mid-century") and 2090–2095 ("end of century"). Under the assumptions made in this study, the results indicate emissions of all species are projected to increase under both the RCP 4.5 and RCP 8.5 climate scenarios. Implications : This manuscript quantifies emissions of NH3, NOx, and N2 O on a global scale from biomass burning from 2001–2015 then creates regression models to predict emissions based on climate change. Because reactive nitrogen emissions have such an important role in the global nitrogen cycle, changes in these emissions could lead to a number of health and environmental impacts.